Konsep Dasar Analisis Kebijakan dan Problematika Pendidikan - Putri, Anjellie Dasviana; Wahyuni, Sri; Istikarani, Mutya; L, Lisaryadi; Yusup, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Problematics of education always arise and almost try to solve them. However, the various efforts undertaken to develop education are not always going smoothly and seamlessly as there are various obstacles that hinder and hinder the process of such efforts. Therefore, this paper will discuss regarding the basic concepts of policy analysis and educational prolematics. The results of this study show that educational policies are the result of decisions made paying attention to the relationship of education with other social components. Therefore, similar to policy analysis in other areas, this contextual and interdisciplinary character is characteristic of education policy analysis. Policy analysis is an attempt to create and manage (relevant) information by utilizing applied social science. Additionally, in Indonesia there are social and economic challenges that contribute to educational development, such as high poverty rates and constraints in leveling access to education for all strata of society, resulting in inequality in learning opportunities. Regarding this, there are still many inadequate schools so that the educational institutions lag far behind compared to other schools, for example in remote villages.